2019
DOI: 10.3390/md17060375
|View full text |Cite
|
Sign up to set email alerts
|

New Aromatic Bisabolane Derivatives with Lipid-Reducing Activity from the Marine Sponge Myrmekioderma sp.

Abstract: The previously reported 1-(2,4-dihydroxy-5-methylphenyl)ethan-1-one (1), (1’Z)-2-(1’,5’-dimethylhexa-1’,4’-dieny1)-5-methylbenzene-1,4-diol (2), and 1,8-epoxy-1(6),2,4,7,10-bisaborapentaen-4-ol (5) together with four new structures of aromatic bisabolane-related compounds (3, 4, 6, 7) were isolated from the marine sponge Myrmekioderma sp. Compounds 1, 2, and 5 were identified based on spectral data available in the literature. The structures of the four new compounds were experimentally established by 1D and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Our work evidenced the lipid-reducing activity of some extracts (EL, ML) with EC 50 values of 1.2-2.2 µg/mL using the zebrafish Nile red fat metabolism assay as a whole small animal model in vivo. This assay was used previously to show the lipid-lowering effects of extracts of raw materials or marine organisms (wine lee, actinobacteria, cyanobacteria, sponges), or isolated compounds (polyphenols, chlorophyll derivatives) [19][20][21][22][23]. The original paper from Jones et al [24] demonstrated that zebrafish responded to lipid modulator drugs in the same way as humans.…”
Section: Discussionmentioning
confidence: 99%
“…Our work evidenced the lipid-reducing activity of some extracts (EL, ML) with EC 50 values of 1.2-2.2 µg/mL using the zebrafish Nile red fat metabolism assay as a whole small animal model in vivo. This assay was used previously to show the lipid-lowering effects of extracts of raw materials or marine organisms (wine lee, actinobacteria, cyanobacteria, sponges), or isolated compounds (polyphenols, chlorophyll derivatives) [19][20][21][22][23]. The original paper from Jones et al [24] demonstrated that zebrafish responded to lipid modulator drugs in the same way as humans.…”
Section: Discussionmentioning
confidence: 99%
“…Another four new aromatic bisabolanes, including 6-(3-hydroxy-6-methyl-1,5-heptadien-2-yl)-3-methylbenzene-1,4-diol ( 86 ), 4-hydroxy-3,7-dimethyl-7-(3-methylbut-2-en-1-yl)benzofuran-15-one ( 87 ), 6-(2-methoxy-5-methylhept-4-en-2-yl)-3-methylbenzene-1,4-diol ( 88 ), and 9-(3,3-dimethyloxiran-2-yl)-1,7-dimethyl-7-chromen-4-ol ( 89 ), were obtained from an organic extract of the marine sponge Myrmekioderma sp. ( Costa et al, 2019 ). All of the isolated compounds represented cyclic bisabolanes bearing rich oxo functionality.…”
Section: Chemical Diversity Of the Newly-discovered Marine-derived Bi...mentioning
confidence: 99%
“…It appeared that the acetoxy group at C-11 could significantly enhance inhibitory ability against marine phytoplanktons. Zebrafish Nile red fat metabolism assay revealed that compounds 86 , 87 , and 89 had significant lipid-reducing activity with IC 50 values of 7.89, 12.61, and 1.22 μM, respectively ( Costa et al, 2019 ). 92 containing an isonitrile group exerted strong brine shrimp lethal activity with an LC 50 of 0.1 μg/ml ( Iwashima et al, 2002 ).…”
Section: Biological Activities Of Bisabolanesmentioning
confidence: 99%
“…Despite being a rich source of highly bioactive compounds [ 93 ], there are few studies in the literature regarding the extraction and identification of polyphenols in sponges. Methanol and dichloromethane were normally used for extraction, while new phenolic compounds have been identified using HRAPCIMS, HRESIMS and NMR.…”
Section: Marine Phenolics: Sources and Phenolic Compositionmentioning
confidence: 99%